Potensi Fraksi Minyak Sawit Sebagai Pengganti Lemak Kakao Pada Produk Cokelat - Iyola Brilianda; Juana Tamariska Putri Lahagu; Kahfiola Damayanti; Jihan Felisha Putri (Jurnal Agritechno, 2025)
The demand for chocolate continues to increase along with high public consumption. One of the main components in chocolate formulation is fat, which generally comes from cocoa butter. However, the availability of cocoa butter is limited and the price is relatively high, so a more economical and easily obtained substitute material is needed locally to support the sustainability of the chocolate industry. This study aims to examine the potential of palm oil fractions, especially palm stearin and olein, as a partial substitute for cocoa butter (Cocoa Butter Substitute/CBS) in chocolate formulations. The study was conducted through a literature review of scientific journals published in the last 10 years, which included chemical, physical, and sensory analysis data on palm oil-based chocolate products. The results of the study showed that stearin increased the melting point and firmness of the product, while olein produced a softer texture and a smoother melting sensation. Sensorially, olein-based formulations showed a higher level of acceptance than stearin, especially in color, aroma, taste, and texture attributes. In addition, palm oil fractions do not produce trans fats, and are able to maintain the balance of solid and liquid fats, while supporting the stability of the product emulsion. This study shows that palm oil fractions, especially through the right combination of stearin and olein, have great potential as a substitute for cocoa butter without reducing physical or sensory quality, thus supporting the sustainability of chocolate production in the future. Keywords: Palm oil, Stearin, Olein, Cocoa Butter Subtitute, Chocolate